Mobilizing Knowledge via Documentary Filmmaking — Is the Academy Ready? - Petrarca, Diana; Hughes, Janette (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2014)
The predominant form of research dissemination resides in the scholar’s domain, namely academic conferences and peer-reviewed journals. This paper describes how two colleagues and researchers integrated documentary filmmaking with research methods in their respective scholarly work, supporting the case for documentary film as an alternative form of scholarly work and knowledge mobilization outside the walls of the university. The authors add to the ongoing conversation for a more dynamic use of digital video-recording that moves beyond simple data collection and encourage researchers to tap into multimodal forms of expression, specifically digital filmmaking.